Rural energy: Fuelling productivity - Gueye, Moustapha K. (Technical Centre for Agricultural and Rural Cooperation, 2008)
For many ACP countries, increasing agricultural productivity also requires more energy from expensive fuel sources. But several projects in West Africa show that bioenergy could help solve the problem.